A design of non-uniform thickness mould for controlling temperature gradient and S/L interface shape in directionally solidified superalloy blade. (15th February 2017) - Qin, Ling; Shen, Jun; Yang, Gongxian; Li, Qiudong; Shang, Zhao
Abstract: The heat transfer behaviors of turbine blade have been simulated using finite element method in three dimensions. The temperature gradient distribution and the solid/liquid (S/L) interface shape evolution were investigated during directional solidification (DS). Numerical results were compared with experimental results and good agreement was found. The experimental results demonstrate that solidification defects, such as freckles and stray grains, were observed on the platform of the blades. Numerical results indicate that this phenomenon should be attributed to a lower axial temperature gradient and a concave S/L interface shape. In order to overcome the shortcomings, two types of non-uniform thickness mould are designed to obtain higher temperature gradient ahead of S/L interface and flat S/L interface, contributing to reducing or eliminating the solidification defects in the blades during direction solidification. Graphical abstract: Highlights: The non-uniform thickness mould is designed to obtain higher axial temperature gradient ahead of S/L interface in the blade. The solid/liquid interface shape of the blade remains flat during the whole directional solidification. Some solidification defects, such as freckles and stray grains, can be effectivelyreduced by the application of non-uniform thickness mould.